Eighth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
Monitoring Report (PMR) on the Status of Management Implementation Plans (MIPs) in Response to Board-Endorsed IEO Recommendations assesses the progress made over the last year on actions contained in the four MIPs arising from recent IEO evaluations, and another four for which individual management actions were classified as still 'in progress' in the Seventh PMR. Overall, 34 of the 77 actions included in the eight MIPs covered in this PMR remain open. Progress on the actions envisaged in the management implementation plans has been somewhat uneven, with more progress being made on the most recent MIPs. Of the 19 actions that have been implemented over the past year, only three relate to the older management actions. Many of the older actions are more broadly worded, and in many instances have no clear timetable. The actions that are progressing more slowly also tend to involve fundamental changes to institutional culture and practices, and therefore require a continuous, long-term effort. In spite of the slower progress on the older actions, significant advances have been made in several key areas. These include: Fund-wide risk analysis and management; the mainstreaming of macro financial surveillance; training on financial sector topics and macro forecasting; acknowledgement, discussion, and dissemination of information on IMF forecasts; the shift towards increasing reliance on quota resources, relative to borrowing; and the approval of the new Statement of Principles and Best Practices in Self-Evaluation. In addition, the 2015 Staff Survey showed significant improvements in several indicators related to the Fund's internal culture and institutional values. Overall, management and staff appear committed to ensuring that open actions remain on track. Progress on all open actions will be assessed in future PMRs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet